(untitled) (Journal of Educational Sciences, 2026)
This article presents an in-depth study of the psychometric properties of the 2025 Unified National Testing (UNT), which serves as a cornerstone of academic selection in Kazakhstan. The relevance of this work is driven by the imperative to ensure educational equity and assessment objectivity amidst the ongoing reforms in the higher education system. The research objective is to verify the stability of test items and analyze the extent to which territorial and institutional characteristics, such as region of residence and school type, determine an applicant’s final performance. A synthesis of Classical Test Theory (CTT) and Item Response Theory (IRT) forms the methodological framework. Special emphasis is placed on DIF analysis, which allows for the identification of latent test bias across various respondent groups. The findings confirm a steady correlation between a student’s socio-geographic location and their academic achievements, highlighting a statistically significant gap in the quality of preparation between urban and rural areas. The authors conclude that while the tests exhibit high internal validity, institutional factors continue to act as «invisible barriers» to higher education access. The practical significance of this study lies in the potential integration of the findings into the National Testing Center’s development strategy to level educational opportunities across the nation. Keywords: UNT, psychometric analysis, academic inequality, IRT modeling, DIF.